EATURES OF THE FUNCTIONAL STATE OF THE LIVER AND KIDNEYS IN PATIENTS WITH PERITONITIS AND THEIR CHANGES AFTER THE USE OF DIFFERENT METHODS OF SANITATION THE ABDOMINAL CAVITY - Міщук, В. В. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Pulse, 2019)
In 66 patients with peritonitis, 30.3% of which were with local, and the 69.7 – diffuse, were studied the functional state of the liver and kidneys and found that its violation occurred in 80.0% and 91.3% of cases accordingly. Intraoperative abdominal sanitation with 0.1% solution of dezmistyn 1000 ml and 1000 ml of 0,05 % chlorhexidine, led to a significant reduction in blood creatine level and normalization of urea, in local and diffuse peritonitis as well. After the intraoperative sanitation with dezmistyn and chlorhexidine the level of gammaglutamiltransferase was reduced by 1.7 and 1.3 times (p<0,05) accordingly. In patients with diffuse peritonitis under the influence of both intraoperative sanitation solutions protein-synthetic function of the liver was significantly improved. Such changes in the functional state of the liver and kidneys are caused by the reduction of microbial toxemia, decrease of inflammatory mediators that are eliminated from the body under the influence of both abdominal sanitation solutions.